Preservation of Art Style in Interior and Architecture Cultural Heritage Buildings: A Case Study in Hotel Kartika Wijaya & Hotel Niagara Malang - Sri Rachmayanti; Christianto R.; Anak Agung Ayu Wulandari (Bina Nusantara University, 2016)
Kartika Wijaya Hotel and Niagara Hotel-Malang are two heritage buildings, which are well managed to preserve their historical building that, has been established since 1891. We can find good harmony and variety in interior elements and design styles, such as Colonial style, Art Noveau and Art Deco style. The purpose of documentating this heritage building that has different design styles is for those who needed. The data will be classified according to the period of the development of the buildings and characteristics of existing styles. The research objective on Kartika Wijaya hotel building and art styles is to preserve historic buildings in Indonesia, through documentation of interior elements and architectures, and to conducted a study of the interior and architectures elements, interior design ornaments, that founded in historical Kartika Wijaya Hotel and Niagara Hotel in Malang, whose the existence needs to be preserved.